Rethinking Social Work Education for Indigenous Students: Creating Space for Multiple Ways of Knowing and Learning - Ives, Nicole G.; Aitken, Oonagh; Loft, Michael; Phillips, Morgan (First Peoples Child & Family Review, 2007)
McGill University School of Social Work initiated a research project in October 2005 to examine the social work education and ongoing professional needs of the First Nations communities of Kahnawake and Kanehsatake. These communities had previously been served by a 30-credit certiﬁcate program. Using qualitative methodology, the project sought to gather data which would eventually assist in the development of a curriculum and pedagogical approach that would reﬂect the social and cultural reality of these communities as part of the regular BSW program. This paper describes the process, key ﬁndings, and potential next steps for the School.